Can changes in resistance exercise workload influence internal load, countermovement jump performance and the endocrine response?. Issue 2 (17th January 2018) - Hiscock, Daniel J; Dawson, Brian; Clarke, Michael; Peeling, Peter
ABSTRACT: This study examined the influence of differing volume load and intensity (%1 repetition maximum[%1RM]) resistance exercise workouts on session rating of perceived exertion (sRPE) countermovement jump (CMJ) performance and endocrine responses. Twelve participants performed a workout comprising four exercises (bench press, back squat, deadlift and prone bench pull) in randomised order as either power (POW); 3 sets × 6 repetitions at 45%1RM × 3 min inter-set rest, strength (ST); 3 sets × 3 repetitions at 90%1RM × 3 min inter-set rest, or hypertrophy (HYP); 3 sets × 10 repetitions at 70%1RM × 1 min inter-set rest in a randomised-crossover design. CMJ performance and endocrine responses were measured immediately pre-, post-, 12, 24, 48 and 72 h post-exercise. POW sRPE (3.0 ± 1.0) was lower than ST (4.5 ± 1.0) ( P  = 0.01), and both were lower than HYP (8.5 ± 1.0) ( P  = 0.01). Duration of CMJ decrement was longer ( P  ≤ 0.05) for HYP (72 h) compared to POW (12 h) and ST (24 h). Testosterone concentration was greater ( P  ≤ 0.05) immediately post-exercise in HYP compared to POW and ST. In conclusion, less inter-set rest, greater volume load and intensity (%1RM) may increase sRPE, duration of CMJ performance decrement and testosterone responses in resistance exercise.